Effect of Low Nighttime Temperature on Oil Accumulation of Rapeseed Seeds (Brassica napus L.) Based on RNA-Seq of Silique Wall Tissue - Chao Mi; Yanning Zhao; Xuetao Yang; Liangbin Lin; Jinxiong Wang (Agriculture)
This study investigated the impact of nighttime temperature and elevation on the oil and erucic acid content of rapeseed (Brassica napus L.) seeds, focusing on the role of sugar synthesis in the silique wall as a substrate for oil synthesis. Field experiments across different altitudes and controlled low nighttime temperature (LNT) treatments (20/18 °C and 20/13 °C) were conducted. Transcriptome analysis of the silique walls was performed to explore gene expression changes. The results showed that higher altitudes and lower nighttime temperatures significantly increased seed oil and erucic acid content, particularly in strong temperature-sensitive line (STSL) seeds. LNT conditions promoted sucrose synthesis and transport in the silique wall by upregulating genes involved in sugar transport (SUT, SWEET, SUC1) and transcription factors (WRKY51, NAC104). This, in turn, enhanced the substrate availability for oil synthesis in the seeds. Furthermore, genes associated with oil biosynthesis (SAD, FAD2, KAS) were significantly upregulated under LNT, promoting oil accumulation. In conclusion, nighttime temperature is a critical factor influencing oil content in rapeseed seeds. Low nighttime temperatures enhance sucrose transport and gene expression in the silique wall, leading to increased oil synthesis. These findings provide insights for breeding strategies aimed at improving seed oil content under varying climatic conditions.